Dog Ecological Characteristics and Their Association with Rabies-Transmitting Animal Bites in the Sajingan and Entikong Border West Kalimantan: A Cross-Sectional Study - Linta, Sonia Nur; Hernawan, Andri Dwi; Saleh, Ismael; Arfan, Iskandar (Jurnal Epidemiologi Kesehatan Komunitas, 2026)
Background: Rabies endemicity in the border regions of West Kalimantan (Sajingan and Entikong) poses a significant public health risk, yet data on local risk factors remain limited. Understanding the ecological determinants of dogs associated with rabies-transmitting animal bites (GHPR) is crucial for effective control. This study aimed to identify dog ecological factors associated with GHPR incidents in these border areas.Methods: This study utilized an analytical cross-sectional design, conducted from January to March 2024. A sample of 348 respondents (dog owners or heads of households) in the Sajingan and Entikong regions was selected using a purposive sampling technique based on GHPR case high-risk areas. Data were collected through structured questionnaires and analyzed using the chi-square test and multivariate logistic regression.Result: The analysis revealed significant associations between dog sex (p=0.002), ownership status/origin (p=0.001), and dog function (p<0.001) with GHPR incidents. Male dogs, stray (unowned) dogs, and dogs used for hunting were identified as having a significantly higher risk of involvement in bite incidents.Conclusion: Ecological factors are key determinants of GHPR in this border region. This finding implies that generalized rabies control strategies are insufficient. Public health interventions, including targeted mass vaccination and population management (e.g., sterilization), must be specifically prioritized for the sub-populations of male, stray, and hunting dogs to interrupt the transmission chain in this high-risk transboundary area.